Liveable city from the resident‘s perception of urban design quality - Abu Hassan, Nur Rasyiqah (2015)
'Liveability‘ has been debated quite extensively. This is because major cities of the world are experiencing extremely high population growth and this has impacted the cities‘ environment and space composition negatively. In theory, 'liveability‘ is likened to the level of an individual‘s living quality in the city. However, modern development has ignored the basic principles of urban design. This research therefore aims to identify the quality aspects of urban design that influence the liveability of a city. The objective of this research is to study the aspects that influence the design quality of a liveable city, the quality attributes of urban design and the importance of those attributes in making the city liveable. The study area is Kuala Lumpur as it is the only city listed in the world ranking of liveable cities. It focuses on the city‘s physical environmental attributes. The research adopts a case study approach and used the survey research method. The questionnaire was used to collect data from 330 residents. Semistructured interviews were conducted with 15 residents and two government agencies which are the Urban Planning Department and the Performance Management Delivery Unit (PEMANDU). Multistage stratified sampling technique was used to select respondents for the questionnaire survey and semi-structured interviews. Descriptive and inferential statistics were used to analyse the data collected. The findings reveal that appreciation of historical sites and cultural values are the two most important aspects in determining the liveability level of Kuala Lumpur followed by the sense of belonging and lastly, the sense of place. Twenty seven attributes were identified as having a relationship to the residents‘ background. Four major attributes that will promote Kuala Lumpur‘s liveability are use of public transport, the voicing out or articulation of opinions, provision of recreational sites and the heritage memory of historical buildings. In conclusion, the historical and cultural elements of Kuala Lumpur have great influence on the sense of place and belongings for its residents. These elements will also play a major role in promoting Kuala Lumpur as a liveable city in the future.